Characterization and functional analysis of miRNAs in Salvia miltiorrhiza-isolated exosome-like nanoparticles for gastric cancer treatment - Gang Chen; Qinjuan Zhong; Ning Tang (PLoS ONE, 2026)
Background Gastric cancer (GC) is a widespread global malignancy, frequently diagnosed at advanced stages owing to the subtle nature of early symptoms and low screening rates. Consequently, there is an imperative need to investigate innovative strategies for the treatment of GC. Exosomes, originating from various sources, act as natural nanocarriers enriched with numerous bioactive molecules, showcasing potential as groundbreaking treatments for GC. Materials and methods In the present study, exosome-like nanoparticles (ELNs) were successfully purified from Salvia miltiorrhiza Bunge (Danshen) utilizing ultracentrifugation. The impact of these ELNs on human gastric cancer cells (HGC-27) was evaluated via a suite of viability assays, encompassing CCK-8, colony formation, flow cytometry, transwell migration, and wound healing assays. Furthermore, miRNA sequencing was conducted to identify and analyze the highly abundant miRNA within Danshen-derived ELNs, along with its potential biological functions. Results The HGC-27 cells internalized Danshen-derived ELNs (DS-ELNs), which led to a decrease in cell viability. Concurrently, these ELNs exhibited significant inhibitory effects on cell migration, colony formation, and overall progression of GC in vitro. The functional analysis of the miRNAs harbored by these ELNs indicated that they may serve as a potential therapeutic target for GC. Conclusion In summary, these findings have not only comprehensively characterized the miRNAs present in Danshen-derived exosomes but also provided invaluable insights into the molecular mechanisms by which Danshen exerts its effects in mitigating